Plato's 'Republic' An Introduction - McAleer, Sean (Open textbook library., 2020)
This book is a lucid and accessible companion to Plato’s Republic, throwing light upon the text’s arguments and main themes, placing them in the wider context of the text’s structure. In its illumination of the philosophical ideas underpinning the work, it provides readers with an understanding and appreciation of the complexity and literary artistry of Plato’s Republic. McAleer not only unpacks the key overarching questions of the text – What is justice? And Is a just life happier than an unjust life? – but also highlights some fascinating, overlooked passages which contribute to our understanding of Plato’s philosophical thought. Plato’s 'Republic': An Introduction offers a rigorous and thought-provoking analysis of the text, helping readers navigate one of the world’s most influential works of philosophy and political theory. With its approachable tone and clear presentation, it constitutes a welcome contribution to the field, and will be an indispensable resource for philosophy students and teachers, as well as general readers new to, or returning to, the text.